Mensurando habilidades de pensamento científico, crítico e criativo em ciências - Santos, Edson José Santana dos (2020)
The proposition of the National Common Curricular Base (BNCC) for the Brazilian education system ratifies teaching based on skills and abilities, produces a demand for the reformulation of local curricula and, consequently, a need to rethink the assessment instruments so that they align with the new Curriculum Guidelines inspired by the base. Thus, this study aims to build and validate an instrument to assess the development of Scientific, Critical and Creative Thinking skills in the general domain of Sciences. For this, the process of construction and validation of the instrument was anchored in the foundations of psychometry, which suggest three stages: theoretical, empirical and analytical. Thus, the instrument underwent two types of validation, one external (with students and judges) and the other internal (internal consistency analysis and factor analysis). The instrument was administered to a total of 453 students in the 1st and 3rd years of high school (136 in the pilot test and 307 in the final administration). The results of internal consistency, as measured by Cronbach's Alpha, varied from 0.59 in the pilot version to 0.63 in the final version. Factor analysis, on the other hand, showed a composition of factors with little representativeness and conceptual divergences in relation to the items. The results of the analysis indicate that the instrument proposed in this research is not considered validated, even with satisfactory reliability results for research in the Humanities area.